Cashless society: A study on intention to adopt e-wallet by the young adults in Malaysia - Gan, Wei Ni; Lim, Jia Xuan; Lim, Shi Pei; Yoong, Nicole Huai Li; Lim, Rebecca Xinyi (2023)
This study aims to identify factors influencing the adoption of E-Wallets among young adults in Malaysia, drawing on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2). We examine the significance of four factors, including social influence, facilitating conditions, price value, and perceived risk, on the behavioral intention of young adults in Malaysia. Data was collected from 309 young adults aged 18-40 via Google Forms, and a rigorous statistical analysis was conducted using SPSS 29.0 software to examine the reliability, accuracy, and relationship between the independent and dependent variables. Our analysis included multiple linear regression, inferential testing, multicollinearity testing, reliability testing, normality testing, and descriptive analysis. The research results indicate that social influence and facilitating conditions have a positive relationship with the behavioral intention of young adults in Malaysia to adopt E-Wallets, while perceived risk has moderate significance. However, the price value was found to be insignificant. Our research findings provide valuable implications for the government, E-Wallet companies, and academia to address the current state of E-Wallet adoption in Malaysia and promote the uptake of this technology. We also offer recommendations for future researchers to conduct more precise and accurate research in this area, overcoming the limitations of our study. Overall, our study provides new insights into the factors that shape the intention of young adults in Malaysia to adopt E-Wallets and contributes to the ongoing discussion on cashless transactions and financial technology in the country. By understanding the factors that shape the adoption of E-Wallets among young adults, stakeholders can develop effective strategies to promote the uptake of this technology and accelerate the country's transition towards a cashless society.